Socio Demographic Factors Related to Smoking among Rural Adolescent (Delta Medical College Journal, 2014)
Background: Smoking is one of the leading preventable causes of premature death, disease, and disability. Adolescence is the period of physical, psychological and social maturation from childhood to adulthood and adolescent smoking is a continuous process which is related to many disease factors. Objective: To find out the factors related to smoking among rural adolescents. Materials and method: One hundred and fifty one male adolescent aged 13 to 19 years from rural areas were interviewed with a semi-structured questionnaire during January to June 2013, at Dhamrai Upazilla Health Complex, Savar, Dhaka, Bangladesh. The socio demographic details, smoking and depression history were recorded. The Center for Epidemiologic Studies Depression (CES-D) Scale was used to measure the presence of depression. Smoking behavior was measured by a number of questions. Results: Mean(±SD) age of the study subjects was 16.8(±1.9) years. Most of the respondents started smoking around the average age of 14.3 years. The study shows that 64% respondents were smokers. Among smokers 80% were influenced by their friends about smoking. Seventy eight percent of the smokers were suffering from depression while 22% of nonsmokers were depressed (p